Influence of treatment including second molars on final and postretention molar angulation - Luiz Filiphe Gonçalves Canuto; Karina Maria Salvatores de Freitas; Marcos Roberto de Freitas; Rodrigo Hermont Cançado (Dental Press Editora, 2013)
OBJECTIVE: Evaluate axial mesiodistal inclinations of the mandibular molars in orthodontically treated cases, analyzing whether inclusion of second mandibular molars in treatment mechanics has any influence on final and postretention molars angulations. METHODS: The sample comprised 150 panoramic radiographs of 50 patients. Patients were treated with extraction of four first premolars and divided into 2 groups: Group 1 comprised 25 subjects without inclusion of mandibular second molars during orthodontic treatment, whereas Group 2 comprised 25 subjects with inclusion of mandibular second molars. Panoramic radiographs at three observation times were evaluated: pretreatment, posttreatment and postretention. The statistical analysis included one-way analysis of variance (ANOVA) for intragroup evaluation and independent t-tests for intergroup comparisons. RESULTS: Intragroup analysis demonstrated significant uprighting of mandibular first and second molars during treatment in Group 2, which remained stable during the postretention stage. Intergroup comparison demonstrated that Group 2 presented first and second molars significantly more uprighted in relation to Group 1 in both post-treatment and postretention stages. CONCLUSIONS: It was concluded that inclusion of mandibular second molars in the orthodontic mechanics is relevant not only to correct the angulation of these teeth, but also to aid mandibular first molars uprighting.